Intracellular oxygen tension limits muscle contraction‐induced change in muscle oxygen consumption under hypoxic conditions during Hb‐free perfusion. Issue 2 (20th January 2017) - Takakura, Hisashi; Ojino, Minoru; Jue, Thomas; Yamada, Tatsuya; Furuichi, Yasuro; Hashimoto, Takeshi; Iwase, Satoshi; Masuda, Kazumi
Abstract: Under acute hypoxic conditions, the muscle oxygen uptake (m V ˙ O2 ) during exercise is reduced by the restriction in oxygen‐supplied volume to the mitochondria within the peripheral tissue. This suggests the existence of a factor restricting the m V ˙ O2 under hypoxic conditions at the peripheral tissue level. Therefore, this study set out to test the hypothesis that the restriction in m V ˙ O2 is regulated by the net decrease in intracellular oxygen tension equilibrated with myoglobin oxygen saturation (∆Pmb O2 ) during muscle contraction under hypoxic conditions. The hindlimb of male Wistar rats (8 weeks old, n  = 5) was perfused with hemoglobin‐free Krebs–Henseleit buffer equilibrated with three different fractions of O2 gas: 95.0%O2, 71.3%O2, and 47.5%O2 . The deoxygenated myoglobin (Mb) kinetics during muscle contraction were measured under each oxygen condition with a near‐infrared spectroscopy. The ∆[deoxy‐Mb] kinetics were converted to oxygen saturation of myoglobin (Smb O2 ), and the Pmb O2 was then calculated based on the Smb O2 and the O2 dissociation curve of the Mb. The Smb O2 and Pmb O2 at rest decreased with the decrease in O2 supply, and the muscle contraction caused a further decrease in Smb O2 and Pmb O2 under all O2 conditions. The net increase in m V ˙ O2 from the muscle contraction (∆m V ˙ O2 ) gradually decreased as the ∆Pmb O2 decreased during muscle contraction. The results of this study suggest that ΔPmb O2 is a key determinant of the Δm V ˙ O2 . Abstract : The resting intracellular oxygen tension (Pmb O2 ) decreases with the decrease in oxygen supply, and muscle contraction leads the further decrease in the oxygen saturation of myoglobin (Smb O2 ) and Pmb O2 at each O2 condition. Moreover, the net increase in m V ˙ O2 from the muscle contraction (∆m V ˙ O2 ) gradually decreased as the net decrease in Pmb O2 (ΔPmb O2 ) decreased during muscle contraction. The results of this study suggest that ΔPmb O2 is a key determinant of the Δm V ˙ O2